Study of raw material resources of Thymus marschallianus at the territory of the Central Kazakhstan - Akhmetalimova, A.M.; Orazbayeva, P.Z.; Ishmuratova, М.Yu.; Ivasenko, S.A.; Glowniak, K. (Fundamental and Experimental Biology, 2017)
In article the analysis of distribution and raw materials of areal part of Thymus marschallianusat the territory of the Karaganda region is carried out. It is revealed that the thyme lives in thyme, spiraea-thyme, herba varia-filipenduls-thyme, shrubby — herba varia — thyme, cereal — herva varia — thyme and herba varia — thyme communities. The species usually grows on slopes ofhills, along springs, on meadows, in the lowhill decreases, on edges the separate forests, in thickets of bushes. Thyme populations in Mountains Ulytau, Mountains Karkaraly, Mountains Buyratau are noted. The set the area of thickets of Thymus marschallianus at the territory of the Karaganda region is estimated at 85,8 hectares, an operational stock — 40,6 tons, the volume of possible annual collecting raw materials — 17,52 tons. It is possible to conduct collecting raw materials on the 1st site 1 time in 3 years.